2017
DOI: 10.1093/ejcts/ezx248
|View full text |Cite
|
Sign up to set email alerts
|

High-dose methylprednisolone in video-assisted thoracoscopic surgery lobectomy: a randomized controlled trial†

Abstract: Registered at clinicaltrialsregister.eu [7 November 2012, EudraCT 2012-004451-37; https://www.clinicaltrialsregister.eu/ctr-search/trial/2012-004451-37/DK].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…Bjerregaard et al. [ 18 ] compared high‐dose methylprednisolone (125 mg) before surgery with placebo. Baseline analgesia included paracetamol, ibuprofen and gabapentin, supplemented by paravertebral block and an intercostal nerves block, with morphine or a bolus of bupivacaine in the intercostal nerves block given as rescue.…”
Section: Resultsmentioning
confidence: 99%
“…Bjerregaard et al. [ 18 ] compared high‐dose methylprednisolone (125 mg) before surgery with placebo. Baseline analgesia included paracetamol, ibuprofen and gabapentin, supplemented by paravertebral block and an intercostal nerves block, with morphine or a bolus of bupivacaine in the intercostal nerves block given as rescue.…”
Section: Resultsmentioning
confidence: 99%
“…As for methylprednisolone, Bjerregaard et al found that high-dose preoperative intravenous methylprednisolone significantly reduced pain but increased blood glucose levels on the day of surgery in patients undergoing VATS to lobectomy under general anesthesia combined with TPVB and an intercostal catheter. 37 As for dexamethasone, Murphy et al demonstrated that the peak serum glucose concentration occurred about 2 hours after the administration of dexamethasone and serum glucose levels did not significantly differ among the groups receiving dexamethasone at a dose of 4 mg and 8 mg as well as saline at any measurement time point. 38 In our study, even though we excluded patients with contraindications to corticosteroid therapy and used a single intermediate dose of dexamethasone, two patients without diabetes mellitus developed intraoperative hyperglycemia after the administration of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no significant differences in pain scores or opioid consumption during admission. Studies of other procedures have shown conflicting results on the analgesic effects of GCs, with some reporting a reduction in postoperative pain scores 25–27 , and others no difference between groups 28–30 . Apart from explaining the different conclusions in terms of small study populations, differences in doses, outcome measures, and statistical analyses, there are most likely also procedure-specific differences in the magnitude of the inflammatory response and the mechanisms of pain.…”
Section: Discussionmentioning
confidence: 99%